Insulin-like growth factor 1 and insulin-like growth factor binding protein-3 as predictive biomarkers of depression and migraine in obese women - Nearmeen M Rashad; Ahmed F Gomaa; Hanan M Sabry; Amira A Fouad; Shereen M El Shabrawy (SpringerOpen, 2019)
Introduction Obesity and its comorbidity, depression and migraine, are highly prevalent conditions and public health problems of enormous scope that are responsible for the significant quality of life impairment and financial cost. Insulin-like growth factor-1 (IGF-1) and its main binding protein, insulin-like growth factor binding protein-3 (IGFBP-3) are related to metabolic diseases such as growth deficiency, obesity, cancer, neurological, and cardiovascular diseases. The objective of this study was to explore IGF-1 and IGFBP-3 in obesity-associated depression and migraine. Also, we aimed to evaluate the association of IGF-1 and IGFBP-3 with clinical features of depression and migraine. Patients and methods A cross-sectional controlled study included 50 healthy lean control group and 100 obese women who were subdivided into three subgroups: obese without depression and migraine (n=27), patients with depression (n=24), and patients with migraine (n=49). Clinical, neurological, and psychiatric evaluation of all patients was done. We measured IGF-1 and IGFBP-3 by commercial enzyme-linked immunosorbent assay. Results Our study showed a significantly lower level of IGF-1 and IGFBP-3 in obese women compared with lean ones. Even more importantly, obese women with depression as well as migraine had significantly lower IGF-1 and IGFBP-3 than those without depression and migraine. Interestingly, the lower levels of IGF-1 and IGFBP-3 in obese women with depression and migraine were significantly negatively correlated with depression score, BMI, and homeostasis model assessments of insulin resistance. Linear regression analysis test in obese patients showed that BMI and depression scores were independently correlated with serum IGF-1. However, BMI, fasting serum insulin, and depression scores were independently correlated with serum IGFBP-3. Conclusions Obese women with depression and migraine had significantly lower IGF-1 and IGFBP-3 than those without depression and migraine.